2020
DOI: 10.1039/d0fo01575j
|View full text |Cite
|
Sign up to set email alerts
|

The hyperglycemic regulatory effect of sprouted quinoa yoghurt in high-fat-diet and streptozotocin-induced type 2 diabetic mice via glucose and lipid homeostasis

Abstract: Recently, we have proposed that quinoa yoghurt (QY) has the anti-diabetic properties based on an in vitro study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…The AKT signaling pathway takes on a critical function in regulating glucose metabolism and insulin resistance (Huang et al., 2018). And the AMPK signaling pathway controls various metabolic dysfunction, including lipid metabolism in T2D (Obaroakpo et al., 2020). The results revealed that, compared with normal mice, p‐IRS‐1, p‐AKT, and p‐GSK3β levels were markedly decreased by 42.90%, 30.56%, and 54.17% in T2D mice, although these effects were reversed by 78.02%, 19.08%, and 129.30% following high‐dose AAPs administration (Figure 8a–d).…”
Section: Resultsmentioning
confidence: 99%
“…The AKT signaling pathway takes on a critical function in regulating glucose metabolism and insulin resistance (Huang et al., 2018). And the AMPK signaling pathway controls various metabolic dysfunction, including lipid metabolism in T2D (Obaroakpo et al., 2020). The results revealed that, compared with normal mice, p‐IRS‐1, p‐AKT, and p‐GSK3β levels were markedly decreased by 42.90%, 30.56%, and 54.17% in T2D mice, although these effects were reversed by 78.02%, 19.08%, and 129.30% following high‐dose AAPs administration (Figure 8a–d).…”
Section: Resultsmentioning
confidence: 99%
“…There is current interest in encouraging the consumption of quinoa since a number of recent studies have shown beneficial effects on biomarkers of cardiovascular disease risk (e.g. Li et al, 2018;Pourshahidi et al, 2020;Obaroakpo et al, 2020;Karimian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disease resulting from insulin resistance and characterized by hyperglycemia (Obaroakpo et al., 2020). By 2040, more than 6.42 million people are expected to develop this disease (Herman, 2017).…”
Section: Introductionmentioning
confidence: 99%